A 17β-Estradiol–Progesterone Oral Capsule for Vasomotor Symptoms in Postmenopausal Women: A Randomized Controlled Trial. Issue 1 (July 2018) - Lobo, Rogerio A.; Archer, David F.; Kagan, Risa; Kaunitz, Andrew M.; Constantine, Ginger D.; Pickar, James H.; Graham, Shelli; Bernick, Brian; Mirkin, Sebastian
Abstract : OBJECTIVE: To evaluate efficacy, endometrial safety, and overall safety of a single-capsule 17β-estradiol–progesterone (TX-001HR) for treating menopausal moderate-to-severe vasomotor symptoms. METHODS: REPLENISH was a phase 3, 12-month, randomized, double-blind, placebo-controlled, multicenter trial. Women (aged 40–65 years) with vasomotor symptoms and a uterus were randomized to daily estradiol (mg)–progesterone (mg) (1/100, 0.5/100, 0.5/50, or 0.25/50), and women in the vasomotor symptoms substudy (women with moderate-to-severe hot flushes [seven or greater per day or 50 or greater per week]) to those estradiol–progesterone doses or placebo. The primary safety endpoint was endometrial hyperplasia incidence at 12 months in all women (the total population), and the primary efficacy endpoints were frequency and severity changes (from daily diaries) in moderate-to-severe vasomotor symptoms with estradiol–progesterone compared with placebo at weeks 4 and 12 in the vasomotor symptoms substudy. A sample size of 250 women in each active treatment arm with two or less endometrial hyperplasia cases would result in 1% or less annual incidence (upper bound 2.5% or less, one-sided 95% CI). RESULTS: One thousand eight hundred forty-five women were enrolled and randomized from August 2013 to October 2015; 1, 835 received medication (safety population); 1, 255 were eligible for the endometrial safety population; 726 comprised the vasomotor symptoms substudy; their mean age and body mass index were 55 years and 27, respectively; one third were African American. No endometrial hyperplasia was found. Frequency and severity of vasomotor symptoms significantly decreased from baseline with 1 mg estradiol and 100 mg progesterone and 0.5 mg estradiol and 100 mg progesterone compared with placebo at week 4 (frequency: by 40.6 and 35.1 points [1 mg and 100 mg and 0.5 mg and 100 mg, respectively] vs 26.4 points [placebo]; severity: by 0.48 and 0.51 vs 0.34 points) and week 12 (by 55.1 and 53.7 vs 40.2; severity: by 1.12 and 0.90 vs 0.56); 0.5 mg estradiol and 50 mg progesterone improved ( P <.05) frequency and severity at week 12, and 0.25 mg estradiol and 50 mg progesterone frequency but not severity at weeks 4 and 12. CONCLUSION: No endometrial hyperplasia was observed while single-capsule estradiol–progesterone provided clinically meaningfully improvements in moderate-to-severe vasomotor symptoms. This estradiol–progesterone formulation may represent a new option, using naturally occurring hormones, for the estimated millions of women using nonregulatory-approved, compounded hormone therapy. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT01942668. Abstract : An investigational oral formulation containing naturally occurring estradiol and progesterone improves moderate-to-severe vasomotor symptoms in postmenopausal women with no endometrial hyperplasia at 1 year.